The association between screen use and central obesity among children and adolescents: a systematic review and meta-analysis - Mohammad Ghasemirad; Leyla Ketabi; Ehsan Fayyazishishavan; Ali Hojati; Zahra Hosseinzadeh Maleki; Mohammad Hadi Gerami; Mahdi Moradzadeh; Jaime Humberto Ortiz Fernandez; Reza Akhavan-Sigari (BMC, 2023)
Abstract Currently, there is no summative study evaluating the association between central obesity and screen time. This systematic review and meta-analysis aimed to summarize the results of studies evaluating the association between screen time and central obesity among children and adolescents. To this end, we performed a systematic search in three electronic databases, including Scopus, PubMed, and Embase to retrieve the related studies up to March 2021. Nine studies were eligible to be included in the meta-analysis. There was no association between odds of central obesity and screen time [odds ratio (OR) 1.136; 95% CI 0.965-1.337; P = 0.125]; however, waist circumference (WC) was 1.23 cm higher in those with highest screen time versus those in the lowest screen time category [weighted mean difference (WMD) = 1.23; 95% 95% CI 0.342-2.112; P = 0.007; Fig. 3]. Moreover, the possible sources of heterogeneity in the included studies were continent and sample size. No evidence of publication bias was reported. For the first time, the current systematic review and meta-analysis revealed that those with the highest screen time had higher WC compared with those with the lowest screen time. Although, there was no association between odds of central obesity and screen time. Due to the observational design of the included studies, it is impossible to infer the cause-effect relationship. Therefore, further interventional and longitudinal studies are warranted to better elucidate the causality of these associations.